2007
DOI: 10.1016/j.msea.2007.01.118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two-stage sintering process on microstructure and mechanical properties of ODS tungsten heavy alloy

Abstract: Oxide dispersion strengthened (ODS) tungsten heavy alloys have been considered as promising candidates for advanced kinetic energy penetrator due to their characteristic fracture mode compared to conventional tungsten heavy alloy. In order to obtain high relative density, the ODS tungsten heavy alloy needs to be sintered at higher temperature for longer time, however, induces growth of tungsten grains. Therefore, it is very difficult to obtain controlled microstructure of ODS tungsten heavy alloy having fine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Ashby [33] has reported that under quasi-static loading, the yield strength of double-phase alloy is related to the inverse square root of average thickness of soft phase between hard phases because yielding of double-phase alloy begins by deformation of the soft phase. An adapted Hall-Petch relation for WHA was developed by Lee et al [17,18] by assuming deformation of WHA began with deformation of the soft matrix phase, as expressed by the following formula:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashby [33] has reported that under quasi-static loading, the yield strength of double-phase alloy is related to the inverse square root of average thickness of soft phase between hard phases because yielding of double-phase alloy begins by deformation of the soft phase. An adapted Hall-Petch relation for WHA was developed by Lee et al [17,18] by assuming deformation of WHA began with deformation of the soft matrix phase, as expressed by the following formula:…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]. The second route is to add inhibitors (such as oxide dispersoids) to prevent grain growth [12,[16][17][18][19]. The last one is to adopt advanced fast sintering techniques such as microwave sintering [20][21][22] and spark plasma sintering (SPS) [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid grain coarsening, a two-stage sintering cycle followed by heat treatment has been reported by Lee 8 ,et al to have a better control over the microstructure of ODS alloys. In two-stage sintering, solid state sintering (SSS) is carried out between 1300 °C and 1450 °C for 1 h -2 h and then subsequently liquid phase sintering (LPS) between 1465 °C and 1485 °C for 1 h. Solid state sintering results in near full density of the alloy while tungsten grain growth and contiguity can be controlled by using lesser holding time in the liquid phase sintering stage 8 . Densification upto 97 per cent can be achieved after solid state sintering but the microstructure will have contiguous tungsten grains and isolated matrix pools.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the mechanical and the ballistic characteristics of tungsten heavy alloys, there are several approaches, the first, by modifying the composition either by optimizing the proportions of tungsten and the other matrix ingredients (Ni, Fe, …etc.) or by Adding different types of oxides, like yttrium o xides [4][5][6], alu minum o xides [7] and zirconiu m oxides [4]. The second, by optimizing the processing parameters (co mpaction pressure, sintering temperature, time, and at mosphere).…”
Section: Introductionmentioning
confidence: 99%